Analysis of patterns of livestock movements in the Cattle Corridor of Uganda for risk-based surveillance of infectious diseases - Hasahya, Emmanuel; Thakur, K.; Dione, Michel M.; Kerfua, S.D.; Mugezi, I.; Hu Suk Lee (Frontiers Media, 2023)
Introduction: The knowledge of animal movements is key to formulating strategic animal disease control policies and carrying out targeted surveillance. This study describes the characteristics of district-level cattle, small ruminant, and pig trade networks in the Cattle Corridor of Uganda between 2019 and 2021.